2007 Guideline for Isolation Precautions : Preventing Transmission of Infectious Agents in Healthcare Settings / Jane D. Siegel, Marguerite Jackson, Linda Chiarello - Siegel, Jane D.
This document is intended for use by infection control staff, healthcare epidemiologists, healthcare administrators, nurses, other healthcare providers, and persons responsible for developing, implementing, and evaluating infection control programs for healthcare settings across the continuum of care. The reader is referred to other guidelines and websites for more detailed information and for recommendations concerning specialized infection control problems.